Mining booms and sustainable economic growth in Mongolia: Empirical result from recursive dynamic CGE model - Davaajargal Lkhagva; Zheng Wang; Changxin Liu (Economies, 2019)
This research aims to lay out a framework to quantify the impacts of mining booms on the macro-economy in Mongolia, a country that is increasingly dependent upon its mining sector. The study uses a dynamic computable general equilibrium (CGE) model to examine the long-term effects on the economy with three sets of scenarios: (1) a moderate boom in the productivity of agriculture, manufacturing, coal mining and coal service sectors; (2) a drop in the world price of coal and metal ores; and (3) the combination of these two scenarios. We assume that these shocks are seismic, and the findings are important for policymakers to implement policy to deal with the negative impact of mining booms. Our study result shows that reinvestment in the agriculture and manufacturing sectors could help to mitigate the resource curse, and suggests that suitable macroeconomic management and prudent administration of the mining sector's windfall income are important.
Keywords: 330; dynamic CGE model; total factor productivity; natural resources; Mongolia